STEM CELL THERAPY FOR NEUROLOGICAL DISORDERS: A FOCUS ON AGING - Nguyen, Hung (Neurobiol Dis, 2018)
Age-related neurological disorders continue to pose a significant societal and economic burden. Aging is a complex phenomenon that affects many aspects of the human body. Specifically, aging can have detrimental effects on the progression of brain diseases and endogenous stem cells. Stem cell therapies possess promising potential to mitigate the neurological symptoms of such diseases. However, aging presents a major obstacle for maximum efficacy of these treatments. In this review, we discuss current preclinical and clinical literature to highlight the interactions between aging, stem cell therapy, and the progression of major neurological disease states such as Parkinson’s disease, Huntington’s disease, stroke, traumatic brain injury, amyotrophic lateral sclerosis, multiple sclerosis, and multiple system atrophy. We raise important questions to guide future research and advance novel treatment options.